Giudizio riflettente e creazione di concetti. Il debito deleuziano verso Kant (Lebenswelt. Aesthetics and philosophy of experience., 2019)
Is Deleuze really in debt to Kant? If so, in which feature of Deleuze's thought can it be traced?The Deleuzian idea of philosophy meant as a creative process for constructing concepts may be deeply rooted in Kant's thought. In his lectures on Kant held at Vincennes in 1978, he acknowledged that Kant first attributed the act of thinking a new absolute meaning: the power to create concepts and no longer a vague meaning to create images or to remember.According to Deleuze the originality of Kant's philosophy lies in creating new words and giving them a new meaning. Although Deleuze had dedicated Kant a significant study in 1963 and four lectures at Vincennes, he did not fully admit to being influenced by Kant, not even in What is Philosophy?, the last monography he wrote with Félix Guattari.